Enzymatic Synthesis of Sucrose Polyester as Food Emulsifier Compound - Handayani, Sri; Novianingsih, Ika; Barkah, Awaliatul; Hudiyono, Sumi (Makara Journal of Science, 2012)
Sucrose polyester (SPE) is a carbohydrate ester compound that has diverse functions, from surfactant to low-calorie food products. Sucrose fatty acid ester with the degree of substitution 1-3 can be used as emulsifier in foods and cosmetics. The enzymatic synthesis of sucrose polyesters can be carried out using lipase in organic solvent and contain small amount of water. In this study sucrose esters were synthesized by esterification reaction between sucrose with fatty acids from coconut and palm oil using Candida rugosa lipase in n-hexane. Optimization esterification reaction was carried out for parameters of incubation time, temperature, and the ratio of the substrate. The optimum incubation time was at 18 hours for coconut oil and 12 hours palm oil, the optimum temperature was 30 o C for coconut and palm oil, and the mole ratio of fatty acid to sucrose was 40:1 for coconut oil and 64:1 for palm oil. Esterification products were characterized by FT-IR. The FT-IR spectrum showed the ester bond was formed as indicated by the wave number 1739.79/cm. Esterification products have 2 substitution degrees.